2018
DOI: 10.1111/aogs.13349
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endometrial thickness on pregnancy rates in modified natural cycle frozen‐thawed embryo transfer

Abstract: Given that endometrial thickness was not found to be predictive of pregnancy after mNC-FET, cancellation based on endometrial thickness alone may not be justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In all studies published to date, the association of endometrial thickness with pregnancy rate was performed only with high-dose IVF stimulations, cryopreserved embryos (12) or low-dose IUI stimulations. The IVF studies suggested an increase in the pregnancy rate with an endometrium >7 mm (3), whereas the IUI studies failed to demonstrate such a relationship (8).…”
Section: Discussionmentioning
confidence: 99%
“…In all studies published to date, the association of endometrial thickness with pregnancy rate was performed only with high-dose IVF stimulations, cryopreserved embryos (12) or low-dose IUI stimulations. The IVF studies suggested an increase in the pregnancy rate with an endometrium >7 mm (3), whereas the IUI studies failed to demonstrate such a relationship (8).…”
Section: Discussionmentioning
confidence: 99%
“…The study of K.E.Liu et al calculated the ORs and their 95% CIs for ongoing pregnancy outcomes with different cut-off values of EMT, and the authors concluded that ongoing pregnancy likelihood was significantly higher in patients with EMT � 9 mm as compared to those who had EMT 3-8 mm [14]. A retrospective study of FET cycles by Tarek El-Toukhy et al compared patients whose endometrial thickness were < 7 mm, 7-8 mm, 9-14 mm and > 14 mm, and found that those with the endometrial thickness of 9-14 mm on the day of progesterone supplementation had higher rates of implantation and pregnancy rates [5]. As with most of the previous studies, in the study of Zhiqin Bu et al, all patients were classified into three groups (Group A, EMT � 8 mm; Group B, EMT 9-13 mm; Group C, EMT � 14 mm) according to the endometrial thickness on the ET day.…”
Section: Plos Onementioning
confidence: 99%
“…It is noteworthy that this study is the first to report a minimum threshold of endometrial thickness for optimal pregnancy outcomes. Several studies in the past merely reported a relatively broad range of endometrial thicknesses that were considered optimal for pregnancy outcomes while the classification of endometrial thickness in their studies was arbitrary, being mainly based on clinical experience or references [5,9,14], while the range of endometrial thickness in each group was also very large, thus making these studies unlikely of being able to provide good guidance for clinical practice. The result of threshold effect analysis showed that 8.7 mm was the lowest threshold of endometrial thickness for the optimal live birth rate of 50.61%.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Sir, Groenewoud et al recently concluded that endometrial thickness does not predict fertility success in modified natural-cycle frozenthawed embryo transfer (mNC-FET) cycles. 1 They suggest that embryo transfer can be planned regardless of endometrial thickness.…”
Section: Endometrial Thickness In Modified Natural-cycle Frozen-thawementioning
confidence: 99%